2022
DOI: 10.14569/ijacsa.2022.0130767
|View full text |Cite
|
Sign up to set email alerts
|

Grape Leaves Diseases Classification using Ensemble Learning and Transfer Learning

Abstract: Agriculture remains an important sector of the economy. Plant diseases and pests have a big impact on plant yield and quality. So, prevention and early detection of crop disease are some of the measures that must be implemented in farming to save the plants at an early stage and thereby reduce the overall food loss. Grapes are the most profitable fruit, but they are also vulnerable to a variety of diseases. Black Measles, Black Rot, and Leaf Blight are diseases that affect grape plants. Manual disease diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…According to experiments, it was found that the performance of the proposed model in the second experiment, provided better accuracy with 99.38% and a loss of 0.0211 for training and an accuracy of 99.35 % and a loss of 0.019 for testing. This is likely due to the fact that the second experiment had fewer training sets than the first experiment, which allowed the model to learn more effectively and generalize better to new data, which goes beyond the testing accuracy of the studies done by (Tiwari, Divyansh, et al, [14]), (S. L. Sanga et al [17]), and (Hema et al [13] ) as shown in Table 5 With an accuracy of 99.82%, the proposed model's accuracy is just somewhat lower than that of the work of Andrew, et al [16]. However, only 37 million training parameters are utilized in the proposed work, compared to the number of training parameters used in [16].…”
Section: Results Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…According to experiments, it was found that the performance of the proposed model in the second experiment, provided better accuracy with 99.38% and a loss of 0.0211 for training and an accuracy of 99.35 % and a loss of 0.019 for testing. This is likely due to the fact that the second experiment had fewer training sets than the first experiment, which allowed the model to learn more effectively and generalize better to new data, which goes beyond the testing accuracy of the studies done by (Tiwari, Divyansh, et al, [14]), (S. L. Sanga et al [17]), and (Hema et al [13] ) as shown in Table 5 With an accuracy of 99.82%, the proposed model's accuracy is just somewhat lower than that of the work of Andrew, et al [16]. However, only 37 million training parameters are utilized in the proposed work, compared to the number of training parameters used in [16].…”
Section: Results Discussionmentioning
confidence: 83%
“…This is likely due to the fact that the second experiment had fewer training sets than the first experiment, which allowed the model to learn more effectively and generalize better to new data, which goes beyond the testing accuracy of the studies done by (Tiwari, Divyansh, et al, [14]), (S. L. Sanga et al [17]), and (Hema et al [13] ) as shown in Table 5 With an accuracy of 99.82%, the proposed model's accuracy is just somewhat lower than that of the work of Andrew, et al [16]. However, only 37 million training parameters are utilized in the proposed work, compared to the number of training parameters used in [16]. This means that the proposed model requires fewer computational resources to train, can be trained faster, and reduce overfitting.…”
Section: Results Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Pendekatan pembelajaran mendalam menggunakan pembelajaran ansambel berdasarkan tiga arsitektur Convolutional Neural Network (CNN) yang terkenal (Visual Geometry Group (VGG16), VGG19, dan Extreme Inception (Xception)) untuk klasifikasi penyakit daun anggur. Model yang diusulkan dilatih sebelumnya dengan ImageNet dan dianalisis menggunakan kumpulan data Plant Village (PV) dari penyakit daun anggur yang umum (Nader et al, 2022). Penelitian tentang klasifikasi varietas daun anggur menggunakan model DenseNet-30 menunjukkan hasil akurasi terbaik yaitu 98%, didalam penelitian ini akan menggunakan dataset yang sama dengan penelitian sebelumnya akan tetapi menggunakan metode yang berbeda, yaitu InceptionV3 diharapkan mencapai akurasi yang lebih baik.…”
unclassified